Rebuilding research capacity in fragile states: the case of a Somali–Swedish global health initiative: Somali – Swedish Action Group for Health Research and Development - Dalmar, Abdirisak Ahmed (Glob Health Action, 2017)
This paper presents an initiative to revive the previous Somali–Swedish Research Cooperation, which started in 1981 and was cut short by the civil war in Somalia. A programme focusing on research capacity building in the health sector is currently underway through the work of an alliance of three partner groups: six new Somali universities, five Swedish universities, and Somali diaspora professionals. Somali ownership is key to the sustainability of the programme, as is close collaboration with Somali health ministries. The programme aims to develop a model for working collaboratively across regions and cultural barriers within fragile states, with the goal of creating hope and energy. It is based on the conviction that health research has a key role in rebuilding national health services and trusted institutions.